2019
DOI: 10.9734/jeai/2019/v33i430150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rice Husk - Mulch on Soil Water Balance Components under Sorghum and Millet Crops in Maiduguri, Semi Arid Northeast Nigeria

Abstract: A 2 x 3 factorial experiment was conducted at two sites in Maiduguri, Borno State during the 2009 cropping season. The objective was to evaluate the influence of rice husk-mulch on soil water balance components under sorghum and millet crops. The treatments comprised of two test crops (sorghum and millet) and three rates of application (0, 10 and 15 t ha-1) of rice husk mulch, fitted in a split-plot design. The test crops were assigned to the main plot, while the mulch application rates were assigned to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Mulch is the protective layer of a material spread on the soil. Mulch from organic matter will be incorporated naturally into the soil [15] by the activity of worms and other organisms. Out of the very many plant species used as sources of green manures, Tithonia diversifolia has been said to be particularly promising [16].…”
Section: Influence Of Tithonia Diversifolia On Maize (Zea Mays L) Yimentioning
confidence: 99%
“…Mulch is the protective layer of a material spread on the soil. Mulch from organic matter will be incorporated naturally into the soil [15] by the activity of worms and other organisms. Out of the very many plant species used as sources of green manures, Tithonia diversifolia has been said to be particularly promising [16].…”
Section: Influence Of Tithonia Diversifolia On Maize (Zea Mays L) Yimentioning
confidence: 99%
“…Fifteen t/ha mulch rate produced longer panicles and higher stover yield than both 0 and 10 t/ha rates. This observation could be attributed to lower crop evapotranspiration and better microclimate resulting from higher soil surface cover and higher leaf canopy cover under 15 t/ha mulch treatment [31]. Other reasons could be higher soil nutrient content.…”
Section: Crop Growth Indicesmentioning
confidence: 94%
“…Another reason could be improved nutrient status following the application of 15 t/ha mulch. Eze et al [29,30] reported that higher soil organic carbon and total nitrogen contents resulted from 15 t/ha mulch rate. This produced taller plants than 0 and 10 t/ha mulch treatments.…”
Section: Crop Growth Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is affected by various factors, including temperature, solar radiation levels, water and nutrient availability, crop variety, cultivar, and age. Eze et al (2018) highlight the significance of implementing efficient agricultural management techniques to optimise the absorption and utilisation of the limited remaining moisture supply from rainfall. This approach promotes sustainable soil productivity and enhances crop growth and yield.…”
Section: Effect Of Mulch On Soil Residual Moisture Conservation At Di...mentioning
confidence: 99%